2007
DOI: 10.1590/s1415-790x2007000100002
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated to knowledge and opinion of gynecologists and obstetricians about the Brazilian legislation on abortion

Abstract: INTRODUCTION: Unsafe abortion accounts for about 12% of maternal deaths in Brazil, although many of these women could meet the requirements for legal abortion in this country. Physicians' inappropriate knowledge of the law may be playing a role in this situation. OBJECTIVE: To evaluate which factors are associated with the level of information and the opinion of the Brazilian gynecologists-obstetricians concerning abortion laws. METHODS: Questionnaires (14.320) were sent to all physicians affiliated to the Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 10 publications
0
12
0
3
Order By: Relevance
“…Em 2012, levantamento do Instituto Anis -Instituto de Bioética, Direitos Humanos e Gênero, encontrou 63 hospitais e clínicas no território nacional que referiram oferecer o programa de abortamento previsto em lei 7 . Entretanto, na prática, os hospitais que efetivamente dispensavam esse atendimento eram em menor número e tinham o acesso dificultado por diversos motivos, entre eles a falta de informação das próprias mulheres e dos provedores de saúde sobre os direitos da mulher à interrupção legal pelo motivo de violência sexual 8,9 . Um estudo que buscou traçar o perfil dos serviços públicos de atendimento à violência sexual descreveu que, dos estabelecimentos que declararam realizar a interrupção legal por motivo de estupro, apenas 5,6% haviam efetivamente realizado pelo menos um procedimento ao longo dos 10-14 meses que antecederam a pesquisa 10 .…”
Section: Introductionunclassified
“…Em 2012, levantamento do Instituto Anis -Instituto de Bioética, Direitos Humanos e Gênero, encontrou 63 hospitais e clínicas no território nacional que referiram oferecer o programa de abortamento previsto em lei 7 . Entretanto, na prática, os hospitais que efetivamente dispensavam esse atendimento eram em menor número e tinham o acesso dificultado por diversos motivos, entre eles a falta de informação das próprias mulheres e dos provedores de saúde sobre os direitos da mulher à interrupção legal pelo motivo de violência sexual 8,9 . Um estudo que buscou traçar o perfil dos serviços públicos de atendimento à violência sexual descreveu que, dos estabelecimentos que declararam realizar a interrupção legal por motivo de estupro, apenas 5,6% haviam efetivamente realizado pelo menos um procedimento ao longo dos 10-14 meses que antecederam a pesquisa 10 .…”
Section: Introductionunclassified
“…When the search criteria were applied, 21 publications were identified, of which 5 were present in both databases, and these duplicates were excluded (Salzano and Shuler-Faccini, 2002;Díaz et al, 2003a, b;Soares, 2003;Faúndes et al, 2004a;Faúndes et al, 2004b;Loureiro and Vieira, 2004;Lunardi and Simões, 2004;Selli, 2004;Goldman et al, 2005;Corrêa and Guilam, 2006;Faúndes et al, 2007a;Faúndes et al, 2007b;Gesteira et al, 2008;De Zordo and Mishtal, 2011;Silva and Araújo, 2011). Thus, 16 publications were finally included in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The 16 publications described only 12 different studies because Faúndes and collaborators showed different results from the same study in 4 publications (Faúndes et al, 2004a;Faúndes et al, 2004b;Faúndes et al, 2007a;Faúndes et al, 2007b), and Diaz and collaborators in two (2003a, b). With regard to language, 6 articles were written in English and 10 in Portuguese.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations